Long-term tolerance to allogeneic thymus transplants in complete DiGeorge anomaly - Chinn, Ivan K (Clinical immunology (Orlando, Fla.), 2008)
Thymus transplantation in subjects with complete DiGeorge anomaly using postnatal allogeneic HLA-nonmatched cultured thymus tissue provides immunoreconstitution. Tolerance of the newly developed T cells toward the donor thymus has not previously been studied. Mixed lymphocyte cultures were used to test 12 thymus transplant recipients for long-term tolerance toward their thymus allografts. Two subjects tested for responses toward thymus donor peripheral blood mononuclear cells showed significantly less reactivity toward the donors compared to responses against third-party allogeneic cells. Peripheral blood mononuclear cells from 10 other subjects were less responsive toward cryopreserved donor thymic cells than toward allogeneic cells (P=0.00007). Adult control peripheral blood mononuclear cells proliferated strongly in response to the donor thymic cells. Both the subjects and controls showed similar proliferative responses against allogeneic cells and phytohemagglutinin. This study provides in vitro evidence for long-term tolerance of complete DiGeorge anomaly thymus transplantation recipients toward their HLA-nonmatched thymus grafts